2002
DOI: 10.1063/1.1448290
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics and thermodynamics of magnetic and dielectric systems based on magnetization and polarization fluctuations: Application of the quasi-Gaussian entropy theory

Abstract: Theoretical equations of state for temperature and electromagnetic field dependence of fluid systems, based on the quasi-Gaussian entropy theory On the use of the quasi-Gaussian entropy theory in noncanonical ensembles. I. Prediction of temperature dependence of thermodynamic propertiesThe quasi-Gaussian entropy ͑QGE͒ theory employs the fact that a free-energy change can be written as the moment-generating function of the appropriate probability distribution function of macroscopic fluctuations of an extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…Results for the permittivity r are presented in Table I for different values of applied potential. At low voltage, we obtain a value of r = 68.1 in agreement with previous values computed by MD by several groups [24][25][26]. When the applied potential increases, the computed dielectric constant decreases, which is a known effect due to saturation of the dielectric material [4,24].…”
supporting
confidence: 89%
“…Results for the permittivity r are presented in Table I for different values of applied potential. At low voltage, we obtain a value of r = 68.1 in agreement with previous values computed by MD by several groups [24][25][26]. When the applied potential increases, the computed dielectric constant decreases, which is a known effect due to saturation of the dielectric material [4,24].…”
supporting
confidence: 89%
“…We considered the external electric field as acting on each atom in the simulation domain without depolarization terms, i.e., under tinfoil boundary conditions [Yeh and Berkowitz, ; Apol et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…In this article we will use the same general notation of electromagnetic ͑em͒ properties as in Ref. 6 ͑hereafter referred to as I͒. For an ellipsoidal system containing N molecules at temperature T and volume V, with a homogeneous external electromagnetic field F 0 aligned along one of the ellipsoidal axes, the canonical partition function is given by 6 Qϭ ͚ n e Ϫ␤͓E n ͑ 0 ͒ ϪM n ЈF 0 ϩ 1…”
Section: A Basic Definitions and Derivationsmentioning
confidence: 99%
“…So far the QGE theory provided theoretical models for the thermodynamics as a function of temperature, [1][2][3][4] density, 5 pressure, 5 and external field, 6 by modeling the dis-tributions of appropriate macroscopic fluctuations by ''quasi-Gaussian'' distributions, i.e., via the convolution of distributions corresponding to identical and statistically independent subsystems. 1,6 Application of the QGE theory to many different systems showed that relatively simple models can describe with high accuracy the thermodynamics of both solids 3 and fluids. 1,4,7,8 In this paper we will illustrate how the QGE theory can be extended towards theoretical models that describe the thermodynamics as a function of two state variables ͑''bivariate'' models͒.…”
Section: Introductionmentioning
confidence: 99%